Measurement of Heavy Metal Mercury (Hg) Content in Catfish (Clarias batrachus) from Rawa Taliwang Lake West Sumbawa - Permatasari, Tri Lintang; Khairuddin, Khairuddin; Yamin, M. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Rawa Taliwang is one of the major lakes in West Sumbawa Regency and is vulnerable to mercury (Hg) contamination resulting from surrounding activities such as illegal gold mining, agricultural runoff, and domestic waste disposal. This study aimed to determine the mercury concentration in catfish (Clarias batrachus) inhabiting the lake and to assess its safety for human consumption. Fish samples were collected from two sampling stations using purposive sampling and analyzed in the laboratory using a Mercury Analyzer. The measured mercury concentrations ranged from 0.058 to 0.086 mg/kg, with an average of 0.072 mg/kg, which is below the maximum allowable limit of 0.50 mg/kg set by the Indonesian National Agency for Drug and Food Control (BPOM) Regulation No. 9/2022. These results indicate that catfish from Rawa Taliwang Lake remain safe for consumption. Continued monitoring and improved environmental management are recommended to prevent future increases in mercury contamination and to ensure long-term ecosystem and public health safety.